Self-Management Intervention: What are the Implications for Students’ Academic and Non-Academic Learning? A Systematic Literature Review - Faruq, Faruq; Purwandari, Eny (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This research analyzed the implementation of self-management (SM) strategies, an intervention to facilitate academic and non-academic studentsâ€™ learning processes. This systematic literature review used an application named, the Publish or Perish 8 program, with a Scopus index. In this research, the applied inclusion criterion was - recent 5-year published articles from 2017-2022. The researchers used PRISMA 2020 concept model with some stages: 1) identifying the articles, 2) screening the articles, 3) checking the eligibility, and 4) using the articles. The researchers applied meta-synthesis data analysis. The results showed that SM strategy implementation could overcome academic problems, and influence learning continuity, balance, motivation, on-task behavior, and learning outcomes. SM strategy could also manage the students’ non-academic problems, such as improving self-confidence, future-decision responsibility, and social involvement. The effectiveness of the SM strategy should also consider the student achievement levels, the experience of disability, and general and specific circumstances at schools. Thus, this strategy could deal with certain situations so SM strategy formulation must consider the student’s needs.